PHYSIOTHERAPY MANAGEMENT WITH EARLY AND GRADUAL MOBILIZATION IN POST-DOUBLE VALVE REPLACMENT SURGERY - Pramudya Putri, Anggun; Isnaini Herawati; Purnomo Gani (CV. Fahr Publishing, 2025)
This study evaluates the effects and importance of post- and post-operative physiotherapy interventions for heart valve replacement to help patients recover their functional abilities. This study was conducted using a case report method where researchers involved a male patient who was treated at DR Kariadi General Hospital Semarang with heart valve disorders. The evaluation used was measuring the patient's vital signs before and after the intervention, measuring the degree of shortness of breath with the Borg scale, measuring pain using the numeric pain rating scale (NPSR), measuring thoracic mobility using the midline, measuring functional ability with the ICU Mobility Scale. Physiotherapy interventions provided were education and breathing exercises before valve surgery and post-operative exercises for respiratory valve replacement including pursed-lip breathing, huffing, and thoracic expansion exercises. The results showed an increase in the physiotherapy intervention given at (T0-T3) where there was an increase in patient hemodynamics, thoracic mobility, functional ability and a reduction in pain in the incision area, and the degree of shortness of breath. Based on the research results that have been carried out, physiotherapy interventions during pre-operative care include patient education and post-operative care include the influence of increasing thoracic mobility, reducing the degree of shortness of breath, pain in the incision area, and increasing functional activity.